Study of lumbar epidural single versus intermittent injection of 0.5% bupivacaine upon onset, level of blockade & haemodynamics in orthopaedic elective lower limb surgeries - Chuen, Ting Yung (2016)
Background: Hypotension and bradycardia are common side effects of epidural anaesthesia. Speed of epidural injection is a contributing factor. To date, no conclusive study has demonstrated the effects of injection rate upon haemodynamic changes. This study is to compare the effects of different injection rate upon haemodynamic parameters, onset and level of blockade in lower limb surgeries. Methods: This prospective, single-blinded randomized controlled study randomized 66 patients into Group 1 (single-injection group) & Group 2 (intermittent-injection group) to receive 10 ml 0.5% bupivacaine and 100 mcg fentanyl at different injection rate. Measurements of vital signs, epidural blockade were taken for 30 minutes. The primary objective is to compare the differences in blood pressure and heart rate between the groups. Other objectives are to compare the differences in onset and level of blockade. Results: Statistical analysis showed significant decrease of mean arterial pressure (MAP) and heart rate in both groups, p < 0.05.However there were no statistically significant in terms of onset of sensory block (p = 0.06), motor block (p= 0.37) as well as level of sensory (p= 0.86) and motor (p= 0.32) blockade in both groups. Conclusions: This study showed epidural injection rate produced significant declines of MAP & heart rate but no difference in term of onset & level of both sensory & motor blockades.